Experimental assessment of inter-centre variation in stopping-power and range prediction in particle therapy. (October 2021) - Peters, Nils; Wohlfahrt, Patrick; Dahlgren, Christina V.; de Marzi, Ludovic; Ellerbrock, Malte; Fracchiolla, Francesco; Free, Jeffrey; Gomà, Carles; Góra, Joanna; Jensen, Maria F.; Kajdrowicz, Tomasz; Mackay, Ranald; et al.
Highlights: First experimental quantification of SPR prediction variation in 17 European centres. Large inter-centre SPR variation 2 σ of up to 9% for bones in the head observed. Variation in range prediction on the magnitude of current clinical safety margins. Observed variation stress the need for a common standard in SPR prediction. Abstract: Purpose: Experimental assessment of inter-centre variation and absolute accuracy of stopping-power-ratio (SPR) prediction within 17 particle therapy centres of the European Particle Therapy Network. Material and methods: A head and body phantom with seventeen tissue-equivalent materials were scanned consecutively at the participating centres using their individual clinical CT scan protocol and translated into SPR with their in-house CT-number-to-SPR conversion. Inter-centre variation and absolute accuracy in SPR prediction were quantified for three tissue groups: lung, soft tissues and bones. The integral effect on range prediction for typical clinical beams traversing different tissues was determined for representative beam paths for the treatment of primary brain tumours as well as lung and prostate cancer. Results: An inter-centre variation in SPR prediction (2σ) of 8.7%, 6.3% and 1.5% relative to water was determined for bone, lung and soft-tissue surrogates in the head setup, respectively. Slightly smaller variations were observed in the body phantom (6.2%, 3.1%, 1.3%). This translated into inter-centre variation of integral range prediction (2σ) of 2.9%, 2.6% and 1.3% for typical beam paths of prostate-, lung- and primary brain-tumour treatments, respectively. The absolute error in range exceeded 2% in every fourth participating centre. The consideration of beam hardening and the execution of an independent HLUT validation had a positive effect, on average. Conclusion: The large inter-centre variations in SPR and range prediction justify the currently clinically used margins accounting for range uncertainty, which are of the same magnitude as the inter-centre variation. This study underlines the necessity of higher standardisation in CT-number-to-SPR conversion.